Molecular Characterization of Salmonella Serovars Anatum and Ealing Associated with Two Historical Outbreaks, Linked to Contaminated Powdered Infant Formula - Gunn, Lynda; Finn, Sarah; Hurley, Daniel; Bai, Li; Wall, Ellen; Iversen, Carol; Threlfall, John E.; Fanning, Séamus (Frontiers in Microbiology, 2016)
Powdered infant formula (PIF) is not intended to be produced as a sterile product unless explicitly stated and on occasion may become contaminated during production with pathogens such as Salmonella enterica. This retrospective study focused on two historically reported salmonellosis outbreaks associated with PIF from the United Kingdom and France, in 1985 and 1996/1997. In this paper, the molecular characterization of the two outbreaks associated Salmonella serovars Anatum and Ealing is reported. Initially the isolates were analysed using pulsed-field gel electrophoresis (PFGE), which revealed the clonal nature of the two outbreaks. Following from this two representative isolates, one from each serovar was selected for whole genome sequencing (WGS), wherein analysis focused on the Salmonella pathogenicity islands. Furthermore, the ability of these isolates to survive the host intercellular environment was determined using an ex vivo gentamicin protection assay. Results suggest a high level of genetic diversity that may have contributed to survival and virulence of isolates from these outbreaks.